GE_GERICHTE P/18166/2019 vom 12. August 2022 - GE Cour de justice (2022)
DÉNONCIATION CALOMNIEUSE;CONTRAINTE(DROIT PÉNAL);TENTATIVE(DROIT PÉNAL);IN DUBIO PRO REO;ERREUR SUR LES FAITS(DROIT PÉNAL);ERREUR DE DROIT(DROIT PÉNAL);DÉTRESSE PROFONDE;PROFOND DÉSARROI;INDEMNITÉ(EN GÉNÉRAL) | CP.181; CP.303.al1.ch1; CP.22; CP.13; CP.21; CP.52; CP.48.leta.ch2; CP.48.letc; CPP.433.al1